(untitled) (Journal of Applied Oral Science, 2022)
Filling materials should be restricted to the root canal space. However, sometimes it is impossible to control the apical extrusion, in this case, the fate of the filling material and the result of the treatment will depend on its physicochemical properties and biocompatibility. Objective: To evaluate the tissue response and bone repair capacity of endodontic sealers that were implanted in the calvaria of Wistar rats, forming the groups (n=16): AH Plus and Sealer Plus, compared to the clot group. Methodology: On days 30 and 60, the animals were euthanized, the calvaria was removed and processed for hematoxylin-eosin, immunohistochemistry for collagen type I, Picrosirus red and microtomographic analysis. Data were subjected to ANOVA and Tuckey tests (p<0.05). Results:At 30 days, all groups showed an intense inflammatory reaction (p>0.05). At 60 days, the AH Plus and Sealer Plus maintained an intense inflammatory infiltrate compared to the clot group (p<0.05). We observed immunopositive areas for type I collagen in all groups at 30 days and 60 days (p>0.05). We observed more red collagen fibers for the Sealer Plus compared to the clot group at 30 days (p<0.05). Considering the total fibers, the clot group at 30 days compared to 60 days after surgery showed an increase in the amount of matrix (p<0.05). There were no statistical differences between groups for green and yellow fibers (p>0.05). Regarding morphometric parameters, at 30 days, the newly formed bone volume and number of bone trabeculae were higher in the groups with sealers compared to the clot group (p<0.05). At 60 days, AH Plus and Sealer Plus showed greater bone neoformation compared to the clot group (p<0.05). Conclusions: Despite AH Plus and Sealer Plus induced an intense inflammatory reaction, they can be considered biocompatible materials, since they allowed bone repair.